Effect of the microstructure on the corrosion behavior of dissimilar friction stir-welded 304 austenitic stainless steel and Q235 low-carbon steel joints. (1st July 2022) - Wang, Hongduo; Zhang, Chengwen; Zhou, Zhiyong; Zhang, Yunzi; Wang, Kuaishe; Wang, Wen; Han, Peng; Lu, Yongxin; Li, Xiao; Liu, Yanming; Zhang, Xiaoyong; Zhou, Yong; et al.
Abstract: To investigate the effect of the microstructure on the corrosion behavior of the dissimilar friction stir welded (FSW) joint between 304 stainless steel (SS304) and Q235 low-carbon steel, the microstructure of the joint in this work was characterized by optical microscopy, scanning electron microscopy (SEM), and electron backscatter diffraction. The corrosion behavior in different zones of the joint was evaluated by the electrochemical tests, and the corresponding corrosion morphologies were illustrated via SEM and laser confocal scanning microscopy. According to the results, plenty of low-angle grain boundaries (LAGBs) and a low proportion of twin boundaries (TBs) deteriorated the corrosion resistance on the SS304 side of the joint. The corrosion products of the SS304 side mainly included γ -Fe2 O3, FeCrO4, and Cr2 O3, while those of the Q235 steel side were α -Fe2 O3 and α -FeOOH. The corrosion mechanism in the stir zone (SZ) was galvanic corrosion between proeutectoid ferrite and pearlite on the Q235 steel side, during which the austenite remained uncorroded, whereas the proeutectoid ferrite, pearlite, and bainite were severely corroded. The above results indicated that the uniform distribution of mixed structures and a small area proportion of austenite (cathode) would improve the corrosion resistance in the SZ.